ECONOMIC DECISIONS OF LATVIAN RURAL ENTREPRENEURS: INTERPRETATION OF MODERN SOCIO-ECONOMIC DISCOURSES - Cals, Igo; Sumilo, Erika; Savrina, Baiba; Baumane-Vitolina, Ilona (European Scientific Journal, ESJ, 2013)
The basic assumption of European social science tradition is a conclusion that every decision made by an individual or an organization is well-founded and rational. The uppermost thesis of classical economics is a desire of every economic entity to attain maximum income by applying minimum possible resources. Hereto, income is usually defined by fiscal indices. Modern economics theories confirm that economic decision making processes can be explained more precisely with concepts of behavioural economics. Agents who make economic decisions are “rationally bounded” and elements of social positioning possibly exceed values expressed in categories of economic utility. The objective of this article is to prove that economic decisions made by Latvian rural entrepreneurs can be explained with the help of modern theories of social science that complement classical thought with an interdisciplinary view on socio-economical processes.